PENGARUH KOMPETENSI DAN INDEPENDENSI ACCOUNT REPRESENTATIVE TERHADAP STRATEGI PENGAMANAN PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA KOTA PALEMBANG - Intan Ramadhana (AKUNTABILITAS, 2016)
The purpose of this Research is to analyze the influence of competence and independence Account Representative toward strategy tax reception of security at Pratama Office Service Tax in Palembang City. The Population in this research are KPP Pratama Palembang Ilir Timur, KPP Pratama Palembang Ilir Barat, and KPP Pratama Palembang Sebrang Ulu. The Sample is taken by method ofsaturated sample it's mean all populations are sampled. The Total of questionnaire which is spread are 102 questionnaires. This Research is using analysis test of multiple regression.The result of analysis in this research is to show that the competence of Account Representative has significant effect toward strategy tax reception of security at Pratama office service tax in Palembang city. While Account Representative independence has no significant effect toward strategy tax reception of security at Pratama office service tax in Palembang city. At the same time be competence and independence Account Representative take effect toward strategy tax reception of security at Pratama office service tax in Palembang city.